Factors for Improving Employee Performance in Public Service Organizations in the Aquaculture Sector - Widiya Avianti; Hilman Abdurrahman; Millawati Millawati (Innovation Business Management and Accounting Journal, 2025)
Performance Appraisal System (SKP). According to this regulation, the performance appraisal of civil servants consists of two main aspects, namely the work results achieved and behavioral assessments related to work behavior. It aims to improve the effectiveness and efficiency of civil servant performance appraisals, as well as ensuring that civil servants provide the best public services to the community. Identifying factors that can increase motivation and analyzing performance appraisals that hinder efforts to increase employee motivation within the Organizations in the Aquaculture Sector of Purwakarta Regency. ways to improve employee performance are through training in accordance with their fields, increasing insight through intensive meetings or regular briefings that discuss ongoing work programs, and providing salaries or allowances commensurate with the performance shown by employees. With good work ability, the overall performance of the Organizations in the Aquaculture Sector can improve.